PENGGUNAAN ENTERPRISE ARCHITECTURE PLANNING DALAM PEMODELAN BISNIS PENDIDIKAN DAN PELATIHAN (Studi Kasus: Badan Pendidikan dan Pelatihan Daerah Kab. Lampung Tengah) - Kurniawan, Hendra (244-5567)
Education and Training Agency Central Lampung District has the main task to help organize the housekeeping area by regional authorities in the field of Education and Training and organize helper tasks given by the Provincial Government and the Central Government . Education and Training Agency Central Lampung district as agencies of education and training providers who have the competence to support regional development by creating empowering human resourcesthat are reliable. In order to improve the education and training services, Bandiklatda need to map the business functions within the organization as the primary activities and support activities to provide a basic knowledge of a complete and thorough and consistent . So it is known what is done by each business function. The model used to map business functions using porter value chain and work system framework as a business function decomposition . The results of this study are mapping business functions are reflected in the value chain and work system frameworkKeywords: Business Process Modelling, EAP, Value Chain